Kajian Hadis Tematik dalam Perspektif Historis dan Kontemporer: A Study of Thematic Hadith from Historical and Contemporary Perspectives - Nazula Tsabitania Siswoyo; Muhammad Alif; Mus’idul Millah (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study analyzes thematic hadith as an important tool for understanding and applying Islamic teachings across different periods. It employs a historical approach to trace the emergence and development of thematic hadith studies since the classical era of Islam, including the factors that encouraged early Muslim scholars to utilize and develop hadith in thematic forms. This study investigates how thematic hadith can help connect the intellectual heritage of the past with the needs of contemporary society, facilitating a broader understanding of the teachings of the Prophet Muhammad (peace be upon him). Furthermore, this research examines contemporary perspectives by identifying the relevance and challenges of thematic hadith in the modern era. Globalization, advancements in information technology, and the increasing complexity of socio-religious issues require innovative approaches in hadith studies. This research explores how thematic hadith can function as a bridge linking the intellectual legacy of the past with present societal needs, enabling a more holistic understanding of the teachings of the Prophet Muhammad in the contemporary context. The findings of this study indicate that thematic hadith holds significant potential to overcome the fragmentation of religious understanding and to provide comprehensive guidance for Muslims. By integrating historical and contemporary analyses, this study argues that thematic hadith is not merely a legacy of the past but also a vital instrument for responding to the dynamics of changing times, ensuring that Islamic teachings remain relevant and applicable.